The potential of anti-infectives and immunomodulators as therapies for asthma and asthma exacerbations. - Edwards,MR; Walton,RP; Jackson,DJ; Feleszko,W; Skevaki,C; Jartti,T; Makrinoti,H; Nikonova,A; Shilovskiy,IP; Schwarze,J; Johnston,SL; Khaitov,MR; et al. (Allergy, 2017)
Asthma is responsible for approximately 25,000 deaths annually in Europe despite available medicines that maintain asthma control and reduce asthma exacerbations. Better treatments are urgently needed for the control of chronic asthma and reduction in asthma exacerbations, the major cause of asthma mortality. Much research spanning >20 years shows a strong association between microorganisms including pathogens in asthma onset, severity and exacerbation, yet with the exception of antibiotics, few treatments are available that specifically target the offending pathogens. Recent insights into the microbiome suggest that modulating commensal organisms within the gut or lung may also be a possible way to treat/prevent asthma. The European Academy of Allergy & Clinical Immunology Task Force on Anti-infectives in Asthma was initiated to investigate the potential of anti-infectives and immunomodulators in asthma. This review provides a concise summary of the current literature and aimed to identify and address key questions that concern the use of anti-infectives and both microbe- and host-based immunomodulators and their feasibility for use in asthma.